28Si total body irradiation injures bone marrow hematopoietic stem cells via induction of cellular apoptosis. (May 2017) - Chang, Jianhui; Feng, Wei; Wang, Yingying; Allen, Antiño R.; Turner, Jennifer; Stewart, Blair; Raber, Jacob; Hauer-Jensen, Martin; Zhou, Daohong; Shao, Lijian
Abstract: Long-term space mission exposes astronauts to a radiation environment with potential health hazards. High-energy charged particles (HZE), including 28 Si nuclei in space, have deleterious effects on cells due to their characteristics with high linear energy transfer and dense ionization. The influence of 28 Si ions contributes more than 10% to the radiation dose equivalent in the space environment. Understanding the biological effects of 28 Si irradiation is important to assess the potential health hazards of long-term space missions. The hematopoietic system is highly sensitive to radiation injury and bone marrow (BM) suppression is the primary life‐threatening injuries after exposure to a moderate dose of radiation. Therefore, in the present study we investigated the acute effects of low doses of 28 Si irradiation on the hematopoietic system in a mouse model. Specifically, 6-month-old C57BL/6 J mice were exposed to 0.3, 0.6 and 0.9 Gy 28 Si (600 MeV) total body irradiation (TBI). The effects of 28 Si TBI on BM hematopoietic stem cells (HSCs) and hematopoietic progenitor cells (HPCs) were examined four weeks after the exposure. The results showed that exposure to 28 Si TBI dramatically reduced the frequencies and numbers of HSCs in irradiated mice, compared to non-irradiated controls, in a radiation dose-dependent manner. In contrast, no significant changes were observed in BM HPCs regardless of radiation doses. Furthermore, irradiated HSCs exhibited a significant impairment in clonogenic ability. These acute effects of 28 Si irradiation on HSCs may be attributable to radiation-induced apoptosis of HSCs, because HSCs, but not HPCs, from irradiated mice exhibited a significant increase in apoptosis in a radiation dose-dependent manner. However, exposure to low doses of 28 Si did not result in an increased production of reactive oxygen species and DNA damage in HSCs and HPCs. These findings indicate that exposure to 28 Si irradiation leads to acute HSC damage.